Pelatihan Permainan Tradisional Anak Usia Dini Di TK Kartika VII-14 - Prima, Elizabeth; Putu Indah Lestari (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
Learning activities in early childhood at school basically follow the principle of play-based learning. Various aspects of early childhood growth and development are able to be stimulated when early childhood plays. Traditional games are one of the games that can be applied to early childhood. Traditional games are games belong to a place or city which is a form of regional local wisdom. Traditional games can be introduced to early childhood in learning activities at school as traditional games are capable to develop children's cooperative abilities, sportsmanship, the ability to build strategies, develop dexterity such as running, jumping and balance as well as building early childhood character. However, the problem faced by partners which is TK Kartika VII-14, is the teacher's limited knowledge of traditional games for children therefore they have not been played in learning activities at school. Thus, the PKM Team offered a solution, namely a traditional game workshop for teachers of TK Kartika VII-14. The results of the workshop were that 81.66% of the teachers had knowledge of traditional games and were able to play traditional games.